Principles of electron tunneling spectroscopy - Wolf, E. L. (Oxford : Oxford University Press, 2012)
Electron tunnelling spectroscopy as a research tool has strongly advanced understanding of superconductivity. This book explains the physics and instrumentation behind the advances illustrated in beautiful images of atoms, rings of atoms and exotic states in high temperature superconductors, and summarizes the state of knowledge that has resulted.
Previous ed.: 1985.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Tunneling spectroscopy; Superconductors